2019
DOI: 10.1108/hff-07-2019-0592
|View full text |Cite
|
Sign up to set email alerts
|

A critical review on the applications of fluid-structure interaction in porous media

Abstract: Purpose This study aims to investigate a critical review on the applications of fluid-structure interaction (FSI) in porous media. Design/methodology/approach Transport phenomena in porous media are of continuing interest by many researchers in the literature because of its significant applications in engineering and biomedical sectors. Such applications include thermal management of high heat flux electronic devices, heat exchangers, thermal insulation in buildings, oil recovery, transport in biological tis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 56 publications
(80 reference statements)
0
3
0
Order By: Relevance
“…Throughout the analysis, the physical properties of the fluid are assumed to remain constant, with the exception of density variations that are accounted for using the Boussinesq model. The governing equations used in this investigation are given by [14,17]:…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Throughout the analysis, the physical properties of the fluid are assumed to remain constant, with the exception of density variations that are accounted for using the Boussinesq model. The governing equations used in this investigation are given by [14,17]:…”
Section: Methodsmentioning
confidence: 99%
“…Fluid-structure interaction (FSI) has recently garnered significant attention among researchers in literature. In a study conducted by Khanafer and Vafai [14], FSI was employed to analyze the behavior of porous media. Their results demonstrated that assuming a non-rigid wall condition led to an enhancement in the average Nusselt number.…”
Section: Introductionmentioning
confidence: 99%
“…In turn, the mutual coupling relationship of each phase is realized. The FSI problems exist widely in nature and in the fields of marine engineering, aerospace, and bioengineering [2]. The Tacoma Narrows Bridge in the United States collapsed due to violent chattering during high winds of 19 m/s [3].…”
Section: Introductionmentioning
confidence: 99%